Paradygmat wielkiej dialektycznej syntezy i jego obecność w polskiej socjologii = Paradigm of great dialectical synthesis and its presence in Polish sociology - Wielecki, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The contemporary sociology should be considered in the relation to its past. However, the problem should also be understood in the context of a current deep post-industrial crisis, resulting from enormous civilisation changes, especially technological ones. Moreover, considering the issue one ought to take into account intellectual confusion of many people, a specific evolution of trends of thought, collective imaginaries or systems of values.
Keywords: socjologia; Polska; paradygmat wielkiej dialektycznej syntezy